Enjeux et logiques d’incorporation de mythes du numérique dans l’imaginaire social de la transition énergétique. Le cas de la métropole de Lyon - Virginie CHAPUT (Tic & Société)
The energy transition is one of the great challenges of our century and is presented as an essential lever for reducing greenhouse gas emissions and adapting to climate change. This article examines public policies implemented to make the transition a reality. By proposing a reinterpretation (Jeanneret, 2008) of the notion, these policies help shape the social imaginary. Specifically, we study the integration of discourses around the digital in the deployment of a public energy transition policy, the Energy Master Plan for the metropolis of Lyon. Based on a semantic analysis of the document, this contribution examines how digital myths help construct the social imaginary around the energy transition.